2019
DOI: 10.1002/humu.23735
|View full text |Cite
|
Sign up to set email alerts
|

Where are the missing gene defects in inherited retinal disorders? Intronic and synonymous variants contribute at least to 4% of CACNA1F ‐mediated inherited retinal disorders

Abstract: Inherited retinal disorders (IRD) represent clinically and genetically heterogeneous diseases. To date, pathogenic variants have been identified in ~260 genes. Albeit that many genes are implicated in IRD, for 30–50% of the cases, the gene defect is unknown. These cases may be explained by novel gene defects, by overlooked structural variants, by variants in intronic, promoter or more distant regulatory regions, and represent synonymous variants of known genes contributing to the dysfunction of the respective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
(98 reference statements)
0
17
0
1
Order By: Relevance
“…The variant identified in this study is located in intron 36, two nucleotides away from the splice-site variant c.4294-9G>A associated with CSNB2A. Interestingly, the splice variant c.4294-9G>A was reported to be associated with CSNB2A and leads to a misplicing in an in vitro model: a part of intron 36 is retained [15]. Compared with this CSNB2A variant, the c.4294-11C>G variant may lead to intron retention until the c.4295-10 position ( Figure 3B).…”
Section: Discussionmentioning
confidence: 61%
“…The variant identified in this study is located in intron 36, two nucleotides away from the splice-site variant c.4294-9G>A associated with CSNB2A. Interestingly, the splice variant c.4294-9G>A was reported to be associated with CSNB2A and leads to a misplicing in an in vitro model: a part of intron 36 is retained [15]. Compared with this CSNB2A variant, the c.4294-11C>G variant may lead to intron retention until the c.4295-10 position ( Figure 3B).…”
Section: Discussionmentioning
confidence: 61%
“…CACNA1F-vp also misclassified 125/322 (39%) benign variants (Online Resource 2). A recent study found that disease-implicated CACNA1F variants are present in gnomAD, which might be due to overlooked/ undiagnosed cases in this dataset [53]. When we used a more stringent criterion to define benign variants (presence in the gnomAD dataset in hemizygous state in at least five individuals) we found that the misclassification rate of CACNA1F-vp was lower (16/52; 30%).…”
Section: Discussionmentioning
confidence: 65%
“…The c.3741+2T>C substitution is located on the canonical donor splice site of intron 30, and is expected to cause exon 30 skipping. The p.(Pro1492Ser) variant affects a highly conserved residue and is predicted pathogenic by all in silico tools; further, there are other substitutions at and near position 1492 (p.(Pro1492Ala) and p.(Gly1494Arg)) that have been reported to cause iCSNB [1,42]. The mutation segregated with the disease phenotype in all tested cases (n = 18); among the four cases where segregation analysis was unavailable, two harbored previously reported mutations (case 19: p.(Pro1492Ala) [1,42] and case 21: p.(Arg1502*) [42]) and two harbored novel disease-causing variants (case 9: p.(Val611Glyfs*32) and case 17: p.(Gln1157Gln)).…”
Section: Genetic Resultsmentioning
confidence: 99%
“…The synonymous variant (c.4474C>T; p.(Gln1157Gln)) affects the last nucleotide in exon 28 and is predicted to alter the splice donor site. Recently, two other exonic synonymous variants in CACNA1F (c.646C>T; p.(Leu216Leu) and c.1719G>A; p.(Thr573Thr)) were reported to affect splicing using a minigene approach [42]. In addition, there are reported instances of pathogenic synonymous exonic variants affecting the last nucleotide of an exon leading to a splice site defect in other disorders [86,87].…”
Section: Discussionmentioning
confidence: 99%